"If the glove fits": Hospital-wide universal gloving is associated with improved hand hygiene and may reduce Clostridioides difficile infection. (23rd November 2021) - Prasad, Paritosh; Brown, Lynne; Ma, Shiyang; McDavid, Andrew; Rudmann, Andrew; Lent, David; Reagan-Webster, Patricia; Valcin, E. Kate; Graman, Paul; Apostolakos, Michael
Abstract: Objective: To determine whether a hospital-wide universal gloving program resulted in increased hand hygiene compliance and reduced inpatient Clostridioides difficile infection (CDI) rates. Design: We carried out a multiple-year before-and-after quasi-experimental quality improvement study. Gloving and hand hygiene compliance data as well as hospital-acquired infection rates were prospectively collected from January 1, 2015, to December 31, 2017, by secret monitors. Settings: The University of Rochester Strong Memorial Hospital, an 849-bed quaternary-care teaching hospital. Patients: All adult inpatients with the exception of patients in the obstetrics unit. Interventions: A hospital-wide universal gloving protocol was initiated on January 1, 2016. Results: Hand hygiene compliance increased from 68% in 2015 reaching an average of 88% by 2017 ( P < .0002). A 10% increase in gloving per unit was associated with a 1.13-fold increase in the odds of hand hygiene (95% credible interval, 1.12–1.14). The rates of CDI decreased from 1.05 infections per 1, 000 patient days in 2015 to 0.74 in 2017 ( P < .04). Conclusion: A universal gloving initiative was associated with a statistically significant increase in both gloving and hand hygiene compliance. CDI rates decreased during this intervention.